Kualitas Kehidupan Kerja Petugas Unit Apron Movement Control di Bandar Udara Mopah Merauke - Walid Jumlad; Hertia Rafika Andini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the quality of work life of Apron Movement Control (AMC) officers at Mopah Merauke Airport. The research focuses on four aspects: career development, problem-solving methods, work facilities, and compensation, based on Cascio’s theory (2003). The study employs a qualitative method, conducting interviews with six employees, both civil servants (ASN) and contract workers, to understand their working conditions. The results show that civil servant employees feel fairly satisfied with their quality of work life. They have clear career paths, problem-solving is approached in a familial manner, work facilities are adequate, and the compensation received is considered appropriate. These four factors contribute to their satisfaction and loyalty to the workplace. In contrast, contract employees experience inequality in terms of career development opportunities and compensation, even though their job responsibilities are the same as those of civil servants. This unfairness lowers their work motivation and causes a desire to resign. Limited access to training and a lack of recognition also hinder improvements in their quality of work life. Based on these findings, this study recommends a review of internal policies, particularly regarding career development and the compensation system for non-civil servant employees. The goal is to create a more balanced work fairness and foster a more positive and productive working environment at the AMC Unit of Mopah Merauke Airport.